PENGARUH INTELLECTUAL CAPITAL TERHADAP EARNINGS MANAGEMENT DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Ira Hapsari; Nur Isna Inayati; Anisa Ilma Hartikasari (JURNAL ILMIAH EDUNOMIKA, 2022)
The purpose of this study is to provide empirical evidence regarding the effect of human capital, structural capital, and relational capital which are the three components of Intellectual Capital on Earning Management and how profitability memorization of the relationship. Research data obtained from reports financial year 2015 to 2019 originating from 17 banking companies in Indonesia Purwokerto. The results of hypothesis testing prove that Intellectual Capital with the variables Capital Employed Efficiency, Human Capital Efficiency, and Structured Capital Efficiency can reduce earnings management practices in the company. In addition, profitability can also be found to strengthen relationship between Intellectual Capital and Earnings Management. This proves that the higher the level of profitability, the higher the value of Capital Employed Efficiency, Human Capital Efficiency, and Structured Capital Efficiency so that caused a decline in Earnings Management. Results Based on this research, It is expected that the company will always keep the profitability value stable thereby increasing the value of Intellectual Capital owned and is expected to earnings management practices that can harm the company. Keywords: Efficiency, Intellectual Capital, Earning Management, Profitabilitas